Country-specific assessment of mismanaged plastic packaging waste as a main contributor to marine litter in Europe - Winterstetter, Andrea; Veiga, Joana Mira; Sholokhova, Anastasiia; Šubelj, Gašper (Frontiers in Sustainability, 2023)
Land-based litter and leakages from inadequate waste management are among the primary sources of marine litter. Plastic packaging and small non-packaging plastic items (PPSI) represent the most extensive application of virgin plastics produced and the largest fraction of post-consumer plastic waste. Moreover, PPSI are amongst the top recognizable litter items recorded on European beaches. This study aimed to estimate mismanaged PPSI waste generated in 33 countries in Europe, for the years 2012 and 2018, as well as in coastal territories bordering European seas. The results indicate that most countries generated higher amounts of PPSI waste in 2018, both in absolute amounts and per capita. We estimate that 26.1 million tons of PPSI waste was generated in 2018 in the whole region, corresponding to 42.9 kg per capita (compared to 38.7 kg in 2012). This was also the case for mismanaged PPSI waste, with 3.01 million tons estimated for 2018, compared to 2.90 million tons in 2012, even if most countries managed to reduce their shares of mismanaged PPSI waste. Furthermore, differences in litter pressure around the regional seas are clear, with 90% of the estimated mismanaged PPSI in European coastal territories being generated in the Mediterranean and the Black Sea regions. Limitations related to data gaps and reporting lead to significant uncertainties in our estimations, even if the study made use of officially reported data from European countries. Our study suggests that reductions in the share of mismanaged PPSI waste seem to be mainly driven by efforts at the end-of-life stages of plastics (i.e. waste collection, recycling, disposal), but that these were not sufficient to offset higher amounts of PPSI waste generated in 2018, compared to 2012. Furthermore, exports of plastic waste, including from EU countries, may result in intensified shares of mismanaged PPSI. Responses on both waste management and waste prevention are needed to transition to a circular economy and to reduce the amount of plastic waste that ends up in the marine environment.